2013
DOI: 10.1016/j.bbamem.2012.11.008
|View full text |Cite|
|
Sign up to set email alerts
|

Role of terminal dipole charges in aggregation of α-helix pair in the voltage gated K+ channel

Abstract: The voltage sensor domain (VSD) of the potassium ion channel KvAP is comprised of four (S1-S4) α-helix proteins, which are encompassed by several charged residues. Apart from these charges, each peptide α-helix having two inherent equal and opposite terminal dipolar charges behave like a macrodipole. The activity of voltage gated ion channel is electrostatic, where all the charges (charged residues and dipolar terminal charges) interact with each other and with the transmembrane potential. There are evidences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In an α-helix, the peptide dipoles are aligned in such a way that about 97% of the peptide dipole moments point in the direction of the helix axis [35] (see figure 1(a)). Therefore, α-helices can be regarded as macrodipoles, having a total dipole moment of the order of 3.5N Debye (N is the number of residues), pointing from the negative C-terminus to the positive N-terminus of the helix (see [36] and references therein). The magnitude of the electric dipole of the molecule is not a fixed value but depends on the molecular conformation and on its local environment.…”
Section: Electron Spin Dynamics In a Rigid Helical Moleculementioning
confidence: 99%
“…In an α-helix, the peptide dipoles are aligned in such a way that about 97% of the peptide dipole moments point in the direction of the helix axis [35] (see figure 1(a)). Therefore, α-helices can be regarded as macrodipoles, having a total dipole moment of the order of 3.5N Debye (N is the number of residues), pointing from the negative C-terminus to the positive N-terminus of the helix (see [36] and references therein). The magnitude of the electric dipole of the molecule is not a fixed value but depends on the molecular conformation and on its local environment.…”
Section: Electron Spin Dynamics In a Rigid Helical Moleculementioning
confidence: 99%
“…There is no hard evidence for this assumption except that S3b and S4 are stuck together in all available crystal structures, and our theoretical study has also shown that there is a strong electrostatic interaction between them. [ 8 ] But the exposure of the extracellular and intracellular end of the S3b and S4 helices can be different, due to the flexibility of the paddle and deep water-filled crevices, which have been found by electron paramagnetic resonance (EPR) spectroscopy of an isolated VSD of KvAP. [ 17 ] S3b being in the interior, all the charges (+N3, −C3, -E107 and +H109) are embedded in protein, while on the periphery of the ion channel, S4 α-helix is assumed to be half exposed to the protein and the other half to the dielectric medium of the environment on the helix side.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with our previous report on the role of dipolar terminal charges, which explained that the dipole charges exposed to lipid lowers the PE and these positive and negative half electronic charges on either end of a α-helix are not insignificant. [ 8 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations